Low-dose mycophenolate mofetil improves survival in a murine model of Staphylococcus aureus sepsis by increasing bacterial clearance and phagocyte function - Alby-Laurent, Fanny; Belaïdouni, Nadia; Blanchet, Benoit; Rousseau, Christophe; Llitjos, Jean-François; Sanquer, Sylvia; Mira, Jean-Paul; Pène, Frédéric; Toubiana, Julie; Chiche, Jean-Daniel (Frontiers in Immunology, 2022)
Objectives: Regulators of TLRs signaling pathways play an important role in the control of the pro-inflammatory response that contributes to sepsis-induced tissue injury. Mycophenolate mofetil, an immunosuppressive drug inhibiting lymphocyte proliferation, has been reported to be a regulator of TLRs signaling pathways. Whether MMF used at infra-immunosuppressive doses has an impact on survival and on innate immune response in sepsis is unknown. Methods: C57BL/6J mice were infected intraperitoneally with 108 CFU Staphylococcus aureus, and treated or not with low-dose of MMF (20mg/kg/day during 4 days). Survival rate and bacterial clearance were compared. Cytokine levels, quantitative and qualitative cellular responses were assessed. Results: S. aureus – infected mice treated with MMF exhibited improved survival compared to non-treated ones (48% vs 10%, p<0.001). With the posology used for all experiments, MMF did not show any effect on lymphocyte proliferation. MMF treatment also improved local and systemic bacterial clearance, improved phagocytosis activity of peritoneal macrophages resulting in decreased inflammatory cytokines secretion. MMF-treated mice showed enhanced activation of NF-kB seemed with a suspected TLR4-dependent mechanism. Conclusions: These results suggest that infra-immunosuppressive doses of MMF improve host defense during S. aureus sepsis and protects infected mice from fatal outcome by regulating innate immune responses. The signaling pathways involved could be TLR4-dependent. This work brings new perspectives in pathogenesis and therapeutic approaches of severe infections.